Feasibility of integrating small-scale liquefied natural gas (LNG) terminal with combined cycle power plant to reduce carbon emissions and costs for data centers - Sermsuk, Maytungkorn; Sukjai, Yanin; Rajoo, Srithar; Kiatkittipong, Kunlanan; Wiboonrat, Montri; Siripongdee, Surapong (My University, 2025)
Global data centers are projected to consume 2–3% of global electricity and contribute 8% of carbon emissions by 2030, driven by the rising demand for 5G. In Southeast Asia's tropical climate, cooling data centers presents a challenge, as power plant efficiency drops by 10–20% during summer, when ambient temperatures reach 35–40°C. This study introduces a novel system that integrates a small-scale liquefied natural gas (LNG) receiving terminal with a combined cycle power plant (CCPP) and a data center, designed specifically for tropical climates. The system harnesses LNG cold energy through three configurations: intermediate fluid vaporizer (IFV), Rankine cycle (RC), and direct expansion cycle (DEC), to optimize electricity generation and chilled water production. By reducing the gas turbine inlet temperature from 35°C to 22°C, the system boosts power output by 12.22% and thermal efficiency by 3.84%. Nighttime cooling supports a 3,048-rack data center, resulting in annual savings of $5.50 million and a reduction of 20,304 tons of CO₂ emissions. Switching to gas power plants during summer further increases savings to $7.75 million and cuts emissions by 29,104 tons. An economic analysis shows a payback period of 2.30 years and an internal rate of return (IRR) of 69%. This integrated approach offers an efficient, cost-effective, and environmentally sustainable solution for power generation and data center operation in hot climates.
Keywords: Carbon emissions; Cold energy utilization; Combined cycle power plant (CCPP); Data center; District cooling; Liquefied natural gas (LNG)